2015
DOI: 10.1016/j.ecoenv.2014.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Combined action of estrogen receptor agonists and antagonists in two-hybrid recombinant yeast in vitro

Abstract: a b s t r a c tEstrogen receptor (ER) antagonistic chemicals in aquatic environments are believed to influence the binding of both endogenous and exogenous estrogens to ERs in aquatic organisms. Although the combined effects of estrogenic compounds have attracted much scientific concern, little work has been done on the influence of such antiestrogens on the biological effects of estrogens. This study focused on how the presence of different amounts of antagonists affects the results of ER agonist activity tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The recombinant AR two-hybrid yeast cells were incubated overnight and taken inoculated into SD/-Trp /-Leu culture (1: 10, v:v) to obtain an OD 600 value of 0.75 as previously reported . Then, 200 μL of bacterial suspension containing 0, 0.0625, 0.125, 0.25, 0.5, and 1 μM (equal to 0, 44.13, 88.27, 176.54, 353.07, 706.14 μg/L) TBPH with or without dihydrotestosterone (DHT, 50 nM) was transferred to a 96-well plate and incubated at 37 °C for 2 h. The exposure concentrations of TBPH were determined based on the results of the pre-experiment, and the concentration of DHT was selected according to previous studies. , The contents of DMSO in control, DHT, and TBPH treatments were lower than 0.1% (v/v). Each treatment had three replicate wells ( n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant AR two-hybrid yeast cells were incubated overnight and taken inoculated into SD/-Trp /-Leu culture (1: 10, v:v) to obtain an OD 600 value of 0.75 as previously reported . Then, 200 μL of bacterial suspension containing 0, 0.0625, 0.125, 0.25, 0.5, and 1 μM (equal to 0, 44.13, 88.27, 176.54, 353.07, 706.14 μg/L) TBPH with or without dihydrotestosterone (DHT, 50 nM) was transferred to a 96-well plate and incubated at 37 °C for 2 h. The exposure concentrations of TBPH were determined based on the results of the pre-experiment, and the concentration of DHT was selected according to previous studies. , The contents of DMSO in control, DHT, and TBPH treatments were lower than 0.1% (v/v). Each treatment had three replicate wells ( n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…According to our knowledge, in most cases, the comprehensive estrogenic effect in wastewater samples worldwide generally exhibits estrogenic agonist activities, usually characterized by E 2 -effect equivalent (E 2 -EE) because the antagonist activities are very weak compared to the agonist activities. In theory, the E 2 -EE measured by yeast two-hybrid bioassay is positively correlated with the difference value [(E 2 -BAE) – F ·(4-OHT-BAE)] between the agonist binding activity equivalent and the antagonist binding activity equivalent measured by the developed biosensor, where F represents the E 2 -equivalence factors of 4-OHT, which is as low as approximately 7.3 × 10 –4 . , Therefore, it can be inferred that in most cases, the E 2 -EE can be proportional to the E 2 -BAE due to the 4 orders of magnitude difference in F . Indeed, it could be observed that the E 2 -EE of the above two WWTPs measured by yeast two-hybrid bioassay exhibited a strong linear relationship ( r 2 = 0.991, p < 0.0001) with the E 2 -BAE measured by the developed biosensor (Figure c).…”
Section: Resultsmentioning
confidence: 95%
“…In theory, the E 2 -EE measured by yeast two-hybrid bioassay is positively correlated with the difference value [(E 2 -BAE) − F•(4-OHT-BAE)] between the agonist binding activity equivalent and the antagonist binding activity equivalent measured by the developed biosensor, where F represents the E 2 -equivalence factors of 4-OHT, which is as low as approximately 7.3 × 10 −4 . 38,39 Therefore, it can be inferred that in most cases, the E 2 -EE can be proportional to the E 2 -BAE due to the 4 orders of magnitude difference in F. Indeed, it could be observed that the E 2 -EE of the above two WWTPs measured by yeast two-hybrid bioassay exhibited a strong linear relationship (r 2 = 0.991, p < 0.0001) with the E 2 -BAE measured by the developed biosensor (Figure 4c). Therefore, it was expected that the results of the developed biosensor would be comparable to those of the traditional yeast two-hybrid bioassay in the vast majority of wastewater samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Those structures are useful to understand the structural changes due to agonist and antagonist binding in the ERα LBP. Various computational techniques such as molecular docking [18][19][20][21][22][23][24], MD simulations [25][26][27][28][29][30], predictive modeling [31][32][33][34][35][36][37][38][39][40][41], and in vitro studies were conducted to predict ER binders or non-binders [42,43] and agonists or antagonists [44,45].…”
Section: Introductionmentioning
confidence: 99%